Development Of A Forecast For The Evolution Of Digital Pricing Strategies In The Fmcg Sector Until 2030 (American Economist: Journal of Economics Finance and Global Policy, 2026)
This study focuses on developing a forecast for the evolution of digital pricing strategies in the FMCG sector until 2030. The research examines the growing role of artificial intelligence, big data analytics, cloud computing, and automated pricing systems in transforming modern pricing management practices. Using econometric analysis, trend forecasting, and scenario modeling approaches, the study evaluates the impact of digital pricing technologies on sales growth, profitability, inventory efficiency, and market competitiveness. The findings indicate that enterprises implementing AI-driven and real-time pricing systems are expected to achieve significantly higher operational efficiency and stronger market adaptability compared to firms relying on traditional pricing methods. The research also reveals that personalized pricing and predictive analytics will become key drivers of future pricing competitiveness in the FMCG sector. Furthermore, the study proposes a long-term forecast model that identifies optimistic, moderate, and riskbased scenarios for digital pricing development by 2030. The results provide important practical implications for enterprises seeking to improve strategic pricing management and maintain sustainable competitiveness in increasingly digitalized markets
Keywords: Digital pricing strategies; FMCG sector; dynamic pricing